Gassed up [videorecording (DVD)] - Maddocks, Archie; Skylar, Taz; Skylar, Taz; Odubola, Stephen; Middleburg, Craige (Brainstorm Media, 2024)
Ash, who is trying to earn money to raise his 14-year-old sister and send his mother to rehab, gets caught up with an organized crime ring led by a young and charismatic Albanian immigrant.